A systematic literature review on modular product design. Issue 7 (2nd July 2016) - Bonvoisin, Jérémy; Halstenberg, Friedrich; Buchert, Tom; Stark, Rainer
Abstract : The product architecture has a significant influence on all phases of the product life cycle. Many literature sources claim modular product design offers a large range of advantages for addressing this influence. For example, it enables mass customisation, allows environmentally friendly end-of-life strategies, reduces development costs and allows efficient work in loosely coupled organisations. However, the generally low level of justification of these advantages together with the lack of commonly accepted theoretical references leads to a rather scattered view of the potential of modularisation. Moreover, the diversity of methodological approaches and the lack of common vocabulary represent a challenge for standardisation of practices and may hinder systematic implementation in product development. In particular, more guidance may be required to allow product development teams to choose the right modularisation approach that fits in with their objectives. This article summarises published literature in order to introduce a common language in the field of product modularisation and to build the theoretical basis of a multi-purpose approach – termed 'modularization for X'. It is based on a systematic literature review covering a corpus of 163 publications, provides a structured compilation of drivers, design principles and metrics for modularisation, and identifies challenges for further research efforts.